Human Capital Optimization in Logistics: A Quantitative Analysis of Motivational and Environmental Determinants of Performance - Herdian, Rofik Sandra; Budiyanto, Albert; Nasrullah, Muhammad Nur Cahyo Hidayat; Hariri, Ahmad; Marini (Indonesian Scientific Publication, 2024)
This study investigates the influence of work motivation and work environment on employee performance within PT Aerojasa Cargo's warehouse division. Recognizing the strategic importance of human capital in logistics, the research aims to evaluate how these two variables interact to affect operational outcomes.Using a quantitative methodology, the study surveyed 55 employees selected through Slovin’s formula. A structured Likert-scale questionnaire measured three core constructs: motivation, work environment, and performance. Data were analyzed using SPSS 26.0, employing descriptive statistics, multiple regression analysis, and validation metrics such as Cronbach’s alpha and R². Key results show that both motivation and work environment significantly impact employee performance (p < 0.05), with a combined explanatory power of 83.3% (R² = 0.833). The work environment demonstrated a slightly higher beta coefficient (β = 0.417) than motivation (β = 0.286), suggesting that physical and social workplace conditions are marginally more influential. Descriptive findings also revealed demographic patterns relevant to performance, including age distribution, education level, and gender roles. These findings align with existing literature and underscore the synergistic importance of fostering motivation and creating supportive work environments. The study concludes that HR managers in logistics should implement dual-focused strategies to enhance both motivational drivers and workplace quality. Such strategies may include high-performance work systems, ergonomic improvements, and continuous feedback mechanisms. This research contributes to the field of organizational behavior by offering empirical support for integrated HRM approaches in logistics, providing a framework for future policy and academic inquiry.